Refleksi Hasil PISA (The Programme For International Student Assesment): Upaya Perbaikan Bertumpu Pada Pendidikan Anak Usia Dini) - Hewi, La; Shaleh, Muh (Jurnal Golden Age, 2020)
Abstract Â Â The results of the program for international student assessment (PISA) in 2018 in the category of reading ability, Indonesia ranked 74th out of 79 countries, while for the assessment of mathematical ability and scientific ability, Indonesia ranked 73rd and 71st out of 79 participating countries PISA Achievement of Indonesia's ranking in the PISA assessment has always been constant since the beginning of Indonesia's participation in the assessment from 2000 to 2018. With consistent results that are ranked below bring the consequence of thinking that the quality of Indonesian education is not in accordance with global community standards and below the countries other in the world. Government efforts to make improvements to the results of the PISA assessment are changes in the curriculum, but in reality the results of PISA have not experienced significant changes. This paper is an effort to provide a view on the improvement of PISA results through improving the quality of early childhood education, among others for several reasons, first, the opinions of experts based on the results of their research which found that the development of intellectual abilities reached 80% at an early age so the term which is often used is the golden age (golden age); second, all indicators in the program for international student assessment (PISA) begin to be studied and developed by children in early childhood education institutions ranging from literacy reading (language), mathematical literacy and scientific literacy to be the focus in early childhood learning in institutions PAUD is holistically integrative; third, PAUD access which has not yet covered the whole territory of the Republic of Indonesia, as well as the quality and quality of early childhood education institutions that have not been maximized.Â